2010
DOI: 10.5206/cjsotl-rcacea.2010.1.9
|View full text |Cite
|
Sign up to set email alerts
|

Is "Safety" Dangerous? A Critical Examination of the Classroom as Safe Space

Abstract: The notion that the classroom can, indeed must, be a safe space to promote student engagement and enhance academic outcomes is pervasive in the teaching and learning literature. Despite the prevalence of this claim, there is a dearth of empirical evidence documenting the effectiveness of safe space classrooms in achieving these goals. The purpose of this essay is to provide a critical examination of the classroom as safe space. I begin by deconstructing the common meanings of safety as presented in the pedagog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(50 citation statements)
references
References 17 publications
0
47
0
3
Order By: Relevance
“…Imagine a liberated classroom where a teacher-secure in her own maturing finitude-conveys experiences of personal frailty as a way of fostering awareness of the transience of human accomplishment. Not self-piteous exposés of regrets, but self-aware reflection on the phenomenon of being a limited ego in 18 For a critical examination of the concept of "safe space" in educational settings see Barrett (2010), who argues: "The commonplace, and uncritical, acceptance of safety as a bedrock of quality education is curious, given not only the lack of empirical data to support the effectiveness of the safe classroom in enhancing learning outcomes but also the absence of a precise definition of what exactly safety entails." an expansive universe.…”
Section: A Preferential Option For the Student Qua Studentmentioning
confidence: 99%
“…Imagine a liberated classroom where a teacher-secure in her own maturing finitude-conveys experiences of personal frailty as a way of fostering awareness of the transience of human accomplishment. Not self-piteous exposés of regrets, but self-aware reflection on the phenomenon of being a limited ego in 18 For a critical examination of the concept of "safe space" in educational settings see Barrett (2010), who argues: "The commonplace, and uncritical, acceptance of safety as a bedrock of quality education is curious, given not only the lack of empirical data to support the effectiveness of the safe classroom in enhancing learning outcomes but also the absence of a precise definition of what exactly safety entails." an expansive universe.…”
Section: A Preferential Option For the Student Qua Studentmentioning
confidence: 99%
“…5 Various studies confirm students' need for neutral, nonjudgmental demeanors from professors. See, for example, Barrett (2010) and Latting (1990). Importantly, however, Holley and Steiner's (2005) study found that student traits are far more important than professor traits in creating a productive environment in class.…”
Section: Legitimate Authoritiesmentioning
confidence: 99%
“…Since the 1960s there has been a prevalent belief in the United States that safety in the classroom for all students is not only possible, but also the “ethical obligation” of teachers and school administrators (Barrett :2; Ludlow :2). However, as hooks (:39) points out, even in the absence of explicit antagonism or discomfort, “many students, especially students of color, may not feel at all ‘safe’ in what appears to be a neutral setting”.…”
Section: Paradoxical Safe Space or Safe Space As A Productive Negotimentioning
confidence: 99%
“…Because the phrase has been so widely adopted, “safe space” has arguably become an “overused but undertheorized metaphor” (Barrett :1). In this paper, we undertake precisely this project of retheorizing—or reconceptualizing—safe space.…”
Section: Introductionmentioning
confidence: 99%